PENGARUH NETWORKING CAPITAL , CASH FLOW dan GROWTH OPPORTUNITY TERHADAPRETURN ON ASSET (ROA) DI PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ayu Indriani; Heny Triastuti Kurnia Ningsih; Zenni Riana; Sri Elviani (Universitas Islam Islam Sumatera Utara, 2021)
The purpose of this study was to determine whether Net Working Capital, Cash Flow and Growth Opportunity partially or simultaneously affect the Return On Asset (ROA) of the Textile and Garment Sub-Sector Companies listed on the IDX. Data collection techniques are using secondary data taken from Indonesia Stock Exchange website, Multiple Linear regression Analysis Technique, Hypothesis Test, namely T Test and F Test, Determination Coefficient Test using the SPSS Version 20 application.The results of this study reveal that the Net Working Capital variable partially does not have a significant effect on Return On Asset, the Cash Flow variable partially has no significant effect on Return On Asset, and Growth Opportunity partially has a significant effect on Return On Assets, while the Net Working Capital variable has no significant effect on Return On Asset. Simultaneously, Cash Flow and Growth Opportunity have no effect on Return On Assets.